Pengolahan Limbah Kulit Pisang Menjadi Produk Selai melalui Pelatihan Ekonomi Kreatif Masyarakat Kelurahan Data - sri nur qadri (MALLOMO: Journal of Community Service, 2025)
This community service activity aims to improve the knowledge and skills of residents in Data Village, Pinrang Regency, in utilizing banana peels as value-added food products in the form of jam. The program is expected to support the empowerment of the local creative economy through food diversification while reducing unutilized organic waste. The implementation method included several stages, namely socialization, counseling, demonstration of banana peel jam processing, and direct practice assistance for participants. The analysis technique applied was descriptive qualitative, carried out through observation, interviews, and evaluation of community participation during the activity. The results of the program indicated an increase in participants’ understanding of the entire processing procedure, starting from raw material preparation, cooking techniques, product packaging, up to basic marketing strategies. Participants were also able to produce banana peel jam with acceptable organoleptic quality and good consumer feasibility. The conclusion of this activity is that training in processing banana peels into jam can improve community skills, create new business opportunities, and contribute positively to household income. Therefore, this program has proven effective in promoting community empowerment through the creative and sustainable use of local resources.